2002
DOI: 10.1002/ccd.10122
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary embolism: Angiographic diagnosis and treatment with primary angioplasty

Abstract: Acute coronary embolism is rarely diagnosed and it may explain why normal coronary arteries are found after or even before an acute coronary event in patients with thromboembolic risk factors. Emergency coronary angiography was performed in three patients with prior normal coronary arteries and an acute myocardial infarction, followed by primary angioplasty with low-pressure balloon inflations plus stenting and combined antiaggregation with aspirin, clopidogrel, and abciximab to disrupt the thrombi and protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 10 publications
0
35
0
3
Order By: Relevance
“…In general, the diagnosis of CE has been made based on conventional angiographic features specific for coronary occlusion such as globular filling defects, 16 horse-riding thrombi, 8 or multiple filling defects 33 plus a couple of the following characteristics: (1) no atherosclerotic findings in the coronary trees, (2) presence of predisposing factors or comorbidities (ie, AF, intracardiac prosthesis, infective endocarditis, mural thrombus, or cardiac tumor), or (3) absence of significant stenosis at the culprit lesion after thrombus aspiration.…”
Section: Proposed Criteria For the Clinical Diagnosis Of Cementioning
confidence: 99%
“…In general, the diagnosis of CE has been made based on conventional angiographic features specific for coronary occlusion such as globular filling defects, 16 horse-riding thrombi, 8 or multiple filling defects 33 plus a couple of the following characteristics: (1) no atherosclerotic findings in the coronary trees, (2) presence of predisposing factors or comorbidities (ie, AF, intracardiac prosthesis, infective endocarditis, mural thrombus, or cardiac tumor), or (3) absence of significant stenosis at the culprit lesion after thrombus aspiration.…”
Section: Proposed Criteria For the Clinical Diagnosis Of Cementioning
confidence: 99%
“…For early AMI with ST segment elevation, there are currently two available treatments, intravenous thrombolysis and percutaneous intervention. Some literatures have reported that intravenous thrombolysis could be chosen for the treatment of this kind of coronary (25). Treatment methods using suction to deal with emboli inside the coronary artery have been reported (5,17,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of inadequate anticoagulation acute occlusive embolism to coronary arteries successfully treated with percutaneous transluminal coronary angioplasty (PTCA) in patients with mechanical prosthetic aortic valves has been described in random case reports (7).…”
Section: Discussionmentioning
confidence: 99%